Peningkatan Keaktifan dan Hasil Belajar Materi Keliling dan Luas Bangun Datar Menggunakan Model PBL Siswa Kelas IV SD Muhammadiyah Kemiri - Mahendri, Okti; Widiyono, Yuli; Suyoto, Suyoto (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to enhance the engagement and academic performance of fourth grade students at SD Muhammadiyah Kemiri in the subject of perimeter and area of flat shapes in Mathematics using the Problem Based Learning approach. The findings revealed an increase in students' engagement levels. In the pre-cycle stage, only 37% of students were actively engaged, which rose to 50% in the first cycle's first meeting and 58% in the second meeting, resulting in an average engagement level of 52% in the first cycle. In the second cycle, the engagement levels further improved, with the first meeting reaching 79% and the second meeting reaching 91%, resulting in an average engagement level of 85% in the very active category. Additionally, student academic performance also saw improvement. The percentage of students achieving learning completeness increased from 68% in the pre-cycle stage to 80% in cycle I, a 12% increase, and further to 100% in cycle II, demonstrating significant improvement in the very good category. In conclusion, the implementation of the Problem Based Learning model in teaching Mathematics related to perimeter and area of flat shapes has shown to enhance both student engagement and academic performance in the fourth grade at SD Muhammadiyah Kemiri.